The Neotropical Orthonevra Macquart, 1829 (Diptera: Syrphidae) - Miranda, Gil F. G.; Soares, Matheus M. M.; Thompson, F. Christian (Zootaxa, 2024)
The Neotropical species of the flower fly genus Orthonevra (Diptera: Syrphidae) are revised and 12 new species are described and illustrated: Orthonevra batman sp. nov., O. cthulhu sp. nov., O. gli sp. nov., O. gouletmasnerorum sp. nov., O. hypnotica sp. nov., O. minuosetulata sp. nov., O. nebulosa sp. nov., O. neiae sp. nov., O. roseae sp. nov., O. sternolobosa sp. nov., O. theta sp. nov., and O. thompsoni sp. nov. In addition, seven species are redescribed and illustrated: O. argentina (Brèthes, 1922), O. chilensis Thompson, 1999, O. flukei (Sedman, 1964), O. gewgaw (Hull, 1941), O. neotropica (Shannon, 1925), O. quadristriata (Shannon & Aubertin, 1933) and O. shannoni (Curran, 1926), and three Nearctic (one extending into the Neotropical region) species are diagnosed: O. bellula (Williston, 1882), O. nitida (Wiedemman, 1830) and O. nitidula (Curran, 1925) (for a total of 20 species with Neotropical distribution). Lectotypes are designated for two species, Chrysogater bellulus Williston and C. nitidus Wiedemann, and C. lugubris Jaennicke (1867) is removed from Orthonevra and left incertae sedis. A dichotomous and an interactive pictorial key to these species are also presented.